Dominant strategic archetype of the Russian industrial firm - Igor Gurkov (Journal for East European Management Studies, 2007)
Based on the results of the large-scale survey in Russian industrial enterprises we made an attempt to describe the dominant archetype of the Russian industrial firm in terms of strategic patterns, prevailing corporate trajectories and resulting competitive positioning. We have seen that the dominant archetype based on unrealistic beliefs about the organizational life and wrongly understood standards of social responsibility leads in a majority of cases to ineffective corporate trajectories and suppression of the development potential of quality-oriented companies. – – Basierend auf den Ergebnissen einer breitangelegten Umfrage in russischen Industrieunternehmen wurde der Versuch unternommen, das vorherrschende Modell russischer Industriefirmen bezüglich stategischer Muster, vorherrschender Zielstellungen und daraus resultierender wettbewerbsfähiger Positionierung zu beschreiben. Es wurde herausgefunden, dass das vorherrschende Modell auf unrealistischen Vorstellungen über organisationales Leben und falsch verstandenen Standards sozialer Verantwortung basiert, die in einer Mehrheit der Fälle zu ineffektiven Zielstellungen und zur Unterdruckung des Entwicklungspotentials für qualitätsorientierte Unternehmen führt.
Keywords: 650; dominant archetype; Russian industrial firm; corporate trajectories